2023
DOI: 10.3390/brainsci13060949
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Resting-State EEG Power Spectra and Functional Connectivity after 24 and 36 Hours of Sleep Deprivation

Abstract: Total sleep deprivation (TSD) leads to cognitive decline; however, the neurophysiological mechanisms underlying resting-state electroencephalogram (EEG) changes after TSD remain unclear. In this study, 42 healthy adult participants were subjected to 36 h of sleep deprivation (36 h TSD), and resting-state EEG data were recorded at baseline, after 24 h of sleep deprivation (24 h TSD), and after 36 h TSD. The analysis of resting-state EEG at baseline, after 24 h TSD, and after 36 h TSD using source localization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Previous studies have shown the dose effects of sleep deprivation. As the duration of sleep deprivation is prolonged, cognitive impairment becomes more severe (Doherty et al, 2005;Drummond et al, 2000;Lian et al, 2023;Patel et al, 2008;Shao et al, 2014;Shao et al, 2013). We identified that attention impairment caused by ATSD occurred to varying degrees across the occipital (right inferior occipital gyrus), parietal (bilateral superior parietal lobule), and frontal lobes (left middle frontal gyrus and right inferior frontal gyrus), which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown the dose effects of sleep deprivation. As the duration of sleep deprivation is prolonged, cognitive impairment becomes more severe (Doherty et al, 2005;Drummond et al, 2000;Lian et al, 2023;Patel et al, 2008;Shao et al, 2014;Shao et al, 2013). We identified that attention impairment caused by ATSD occurred to varying degrees across the occipital (right inferior occipital gyrus), parietal (bilateral superior parietal lobule), and frontal lobes (left middle frontal gyrus and right inferior frontal gyrus), which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 90%
“…Wang C. et al, using surface morphological analysis and graph theoretical analysis, showed that sleep restriction decreases cortical thickness and enhances the topological properties of the structural covariance network [43]. Additionally, total sleep deprivation affects functional connectivity, as observed by EEG recordings [48] and event-related potential analysis [49]. However, the impairment induced by sleep deprivation appears to be temporary and reversible with sufficient sleep, as demonstrated by resting-state functional MRI data [50].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged sleep deprivation further exacerbates these effects, with reduced activation in key areas like the prefrontal cortex, posterior parietal cortex, and supplementary motor area during working memory tasks. 105 While the exact nature of these changes – whether they are adaptive responses by the brain to cope with the lack of sleep or direct impairments caused by sleep deprivation – remains unclear, their significant impacts on cognition are evident.…”
Section: The Potential Mechanisms Driving Sd‐induced Pndmentioning
confidence: 99%